TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PEMBUNUHAN BERENCANA DALAM KASUS PEMBUNUHAN BRIGADIR NOFRIANSYAH YOSUA HUTABARAT OLEH FERDY SAMBO, S.H., S.I.K., M.H : Studi Kasus Putusan Pengadilan Negeri Jakarta Selatan No. 796/Pid.B/2022/Pn Jkt.Sel - Putra, Irwan Sapta (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2023)
This study discusses problems related to the crime of premeditated murder committed by the former Head of the Propam Polri Inspector General Pol. Ferdy Sambo, S.H., S.I.K., M.H against his own adjutant Brigadier Nofriansyah Yosua at the Police Service's house. The purpose of this research is to find out 1. What is the motive of the perpetrators of the premeditated murder? 2. What are the criminal sanctions imposed on the perpetrators of the crime of premeditated murder? This research method is normative legal research, with a case study approach based on the decision of the South Jakarta District Court No. 796/Pid.B/2022/PN JKT.SEL. Sources of data in this study using Primary, Secondary and Tertiary data sources. Normative juridical analysis. Research Results 1. The perpetrator's motive for premeditated murder of the victim was based on the story of the perpetrator's wife named Putri Candrawathi who claimed to have been abused by the victim in Magelang, which made the perpetrator angry and killed the victim by shooting the victim with a firearm. 2. The defendant Ferdy Sambo, S.H., S.I.K., M.H., in court has been proven legally and convincingly guilty of committing the crime of "participating in premeditated murder" AND "without the right to take action which results in the electronic system not working properly which was carried out jointly same” as the First Primary Charge and the Second First Primary Charge from the Public Prosecutor, so that the perpetrator by the panel of judges was sentenced to death penalty. Suggestions When we get some information, it is best if the information obtained first is clarified or asked for the truth so that we are not mistaken in taking an action and drawing conclusions. So that it can avoid actions that can be detrimental to both parties.